Autophagy activation attenuates renal ischemia-reperfusion injury in rats - Zhang, Ya-Li (Exp Biol Med (Maywood), 2015)
Ischemia-reperfusion (I/R) injury is a leading cause of acute kidney injury (AKI), which is a common clinical complication but lacks effective therapies. This study investigated the role of autophagy in renal I/R injury and explored potential mechanisms in an established rat renal I/R injury model. Forty male Wistar rats were randomly divided into four groups: Sham, I/R, I/R pretreated with 3-methyladenine (3-MA, autophagy inhibitor), or I/R pretreated with rapamycin (autophagy activator). All rats were subjected to clamping of the left renal pedicle for 45 min after right nephrectomy, followed by 24 h of reperfusion. The Sham group underwent the surgical procedure without ischemia. 3-MA and rapamycin were injected 15 min before ischemia. Renal function was indicated by blood urea nitrogen and serum creatinine. Tissue samples from the kidneys were scored histopathologically. Autophagy was indicated by light chain 3 (LC3), Beclin-1, and p62 levels and the number of autophagic vacuoles. Apoptosis was evaluated by the terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) method and expression of caspase-3. Autophagy was activated after renal I/R injury. Inhibition of autophagy by 3-MA before I/R aggravated renal injury, with worsened renal function, higher renal tissue injury scores, and more tubular apoptosis. In contrast, rapamycin pretreatment ameliorated renal injury, with improved renal function, lower renal tissue injury scores, and inhibited apoptosis based on fewer TUNEL-positive cells and lower caspase-3 expression. Our results demonstrate that autophagy could be activated during I/R injury and play a protective role in renal I/R injury. The mechanisms were involved in the regulation of several autophagy and apoptosis-related genes. Furthermore, autophagy activator may be a promising therapy for I/R injury and AKI in the future.